Understanding Bank Payouts during the Crisis of 2007–2009 - Cziraki, Peter; Laux, Christian; Lóránth, Gyöngyi (The Review of Corporate Finance Studies, 2024)
Abstract We study U.S. banks’ payout policy in 2007–2008. We benchmark these payouts against payouts before the crisis, measure stock price reactions to announcements of dividend changes, and analyze changes in the relation between payout growth and future performance. Further, we examine cross-sectional variation in banks’ payout policy to gauge the possible motives underlying banks’ payout decisions in 2007–2008. We do not find that banks that have a higher willingness to take risk or that have higher incentives to undertake asset substitution use their payout policy to engage in more wealth transfer compared to other banks. (JEL G21, G24, G28, G32, G35). Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.